An exploratory study of pro-inflammatory cytokines in individuals with alcohol use disorder: MCP-1 and IL-8 associated with alcohol consumption, sleep quality, anxiety, depression, and liver biomarkers - Kazmi, Narjis; Wallen, Gwenyth R.; Yang, Li; Alkhatib, Jenna; Schwandt, Melanie L.; Feng, Dechun; Gao, Bin; Diazgranados, Nancy; Ramchandani, Vijay A.; Barb, Jennifer J. (Frontiers in Psychiatry, 2022)
Background High levels of sleep disturbances reported among individuals with alcohol use disorder (AUD) can stimulate inflammatory gene expression, and in turn, may alter pro-inflammatory cytokines levels. We aimed to investigate associations between pro-inflammatory cytokine markers with subjective measures of sleep quality, psychological variables and alcohol consumption among individuals with AUD. Methods This exploratory study is comprised of individuals with AUD (n = 50) and healthy volunteers (n = 14). Spearman correlation was used to investigate correlations between plasma cytokine levels and clinical variables of interest (liver and inflammatory markers, sleep quality, patient reported anxiety/depression scores, and presence of mood and/or anxiety disorders (DSM IV/5); and history of alcohol use variables. Results The AUD group was significantly older, with poorer sleep quality, higher anxiety/depression scores, and higher average drinks per day as compared to controls. Within the AUD group, IL-8 and MCP-1 had positive significant correlations with sleep, anxiety, depression and drinking variables. Specifically, higher levels of MCP-1 were associated with poorer sleep (p = 0.004), higher scores of anxiety (p = 0.006) and depression (p < 0.001), and higher number of drinking days (p = 0.002), average drinks per day (p < 0.001), heavy drinking days (p < 0.001) and total number of drinks (p < 0.001). The multiple linear regression model for MCP-1 showed that after controlling for sleep status and heavy drinking days, older participants (p = 0.003) with more drinks per day (p = 0.016), and higher alkaline phosphatase level (p = 0.001) had higher MCP-1 level. Conclusion This exploratory analysis revealed associations with cytokines MCP-1 and IL-8 and drinking consumption, sleep quality, and anxiety and depression in the AUD group. Furthermore, inflammatory and liver markers were highly correlated with certain pro-inflammatory cytokines in the AUD group suggesting a possible relationship between chronic alcohol use and inflammation. These associations may contribute to prolonged inflammatory responses and potentially higher risk of co-morbid chronic diseases.